Energy intake insufficiency due to underestimated energy requirement by common predictive formulas can be identified by urinary amino acid levels in advanced heart failure - Yoko Sakamoto; Tomohito Ohtani; Kei Nakamoto; Fusako Sera; Shungo Hikoso; Yasushi Sakata (Frontiers in Nutrition)
BackgroundElevated resting energy expenditure (REE) promotes cachexia, worsening prognosis in patients with advanced heart failure (HF). However, adequate assessment of energy balance is challenging because of unvalidated common prediction methods and unestablished determinants of REE, resulting in a lack of biomarkers for predicting insufficient energy intake.ObjectiveThis cross-sectional study aimed to evaluate REE in patients with advanced HF and explore biomarkers for insufficient energy intake.MethodsWe measured REE by indirect calorimetry and calculated the total energy expenditure (TEE) of 72 hospitalized patients with advanced-stage HF. We compared these values with commonly-used formulas and analyzed the associations between REE per body weight (REEBW) and parameters related to hemodynamics and HF severity. In 17 of 72 patients, plasma amino acid (AA) and 24-h urinary AA concentrations were measured to analyze their correlations with energy balance, the ratio of caloric intake to REE.ResultsResting energy expenditure and TEE values were significantly higher than the predicted values. The mean REEBW was 25 kcal/kg/day, while that for the underweight (<18.5 kg/m2) was 28 kcal/kg/day. We found a significant negative correlation between REEBW and body mass index (BMI), but no significant correlation between REEBW and HF-related parameters. The difference between TEE and predicted TEE using the European Society for Clinical Nutrition and Metabolism formula was most significant in the underweight patients because of underestimation, whereas TEE and pTEE using our modified formula with coefficients by BMI categories did not differ. There was a significant correlation between energy balance and urinary histidine and its metabolite 3-methylhistidine excretion, but no significant correlation with serum albumin and other AA concentrations.ConclusionUnderweight patients with advanced HF require more energy per weight than the predicted value. Our proposed formula for pTEE in each BMI category may be useful in clinical practice to avoid underestimation of daily energy requirements. Inadequate energy intake, even with such an approach, may be identified by decreased urinary essential AA levels.